Effect of PM2.5 and its constituents on hospital admissions for cardiometabolic multimorbidity in Urumqi, China - Di Wu; Cheng Li; Yu Shi; Junjie Han; Yaoqin Lu; Yilipa Yilihamu; Yanling Zheng; Liping Zhang (Scientific Reports)
Abstract Cardiometabolic multimorbidity (CMM) is caused by two or more of the diseases ischemic heart disease (CVD), type 2 diabetes mellitus (T2DM), and stroke, and therefore requires more hospitalization and healthcare costs. However, few studies have investigated fine particulate matter (PM2.5) and its constituents and the risk of hospital admissions for CMM. We aimed to study these associations in Urumqi, a representative area in northwest China. The effect of PM2.5 and its constituents on the hospital admissions for CMM was determined using the quantile-based g-computation (QBGC) and bayesian kernel machine regression (BKMR) method, in which the constituents with the greatest effect on the hospital admissions for CMM were ranked as NO3 − > SO4 2− > NH4 + > BC > OM. Among all constituents, NO3 − presented the highest risk, with the largest effect observed at lag 21-day at the maximum concentration (RR = 2.079, 95% CI: 1.396–3.097). Per IQR increase in NO3 − had the significantly effect on hospital admissions for IHD (RR = 1.079, 95% CI: 1.028–1.132) and on hospital admissions for CMM (RR = 1.094, 95% CI: 1.039–1.152). Female patients hospitalized for CMM indicated heightened sensitivity to elevated NO3 − levels (RR = 1.170, 95% CI: 1.077–1.271). The interaction between the high concentrations of PM2.5 and its constituents with low temperature, high relative humidity (RH), and low sunshine duration (SSD) significantly affected hospital admissions for CMM. Additionally, cold waves, defined as the minimum temperature of below P2.5 and sustained for 5 days (CW5), intensified the interaction with PM2.5 and its constituents.